(untitled) (Research, Society and Development, 2023)
This study aimed to analyze the knowledge of primary and secondary school teachers about first aid. Field study, descriptive with a qualitative and transversal approach, developed in a Elementary and High School, located in Regional II of Fortaleza-CE, with the participation of 17 teachers. The data were collected from a form guided by the research question: What is the knowledge of primary and secondary school teachers about first aid? And analyzed by thematic content analysis technique. He realized the precariousness of knowledge about the ways to help a student victim of an accident and the fear of going through situations that involve the need for basic notions of first aid. This study demonstrates the need for a training plan in urgency and emergency with professionals from the school environment, as the knowledge of ways to act in cases of accidents allows the reduction of damages. Nursing plays an important role in health education about first aid at school and can contribute effectively to the training of teachers.